PERAN ORANG TUA DALAM MENDAMPINGI ANAK PADA PEMBELAJARAN DARING KELAS II SD AL-IKHWAN PONDOK AREN - SITI SALWA AGUSTIANA; ANNISA INTANNIA FITRI; LAILY NURMALIA (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This article aims to find out how the role of parents in assisting children in online learning in grade 2 shofa. This writing method uses qualitative methods, and the type of research leads to a phenomenon under study. Focus on the activities of the subject of this research to get data by direct observation. In the current pandemic period, all activities are carried out at home online to avoid the increasing spread of covid-19, including schools, the role of parents is very much needed for the learning process of children during this study from home, but in practice, not all children can run it manually. Fluent. It can be seen that parents feel that learning at home is less effective to implement because parents have their respective activities so that children do not get good supervision when studying and the situation of the online learning process is also burdensome for some parents who are also busy in learning. Work, therefore parents entrust their children to school in order to get maximum guidance from the educators at school. However, situations like this make children less likely to get good tutoring.